2020
DOI: 10.1021/acs.inorgchem.0c01710
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Molar Ratio and Solvent on the Coordination Modes of 1,7-Dibenzyl-4,10-bis(pyridin-4-ylmethyl)cyclen

Abstract: The synthesis of a tetra-armed cyclen (L) with two benzyl groups at the 1- and 7-positions and two pyridin-4-ylmethyl groups at the 4- and 10-positions as side arms and the solvent- and/or molar-ratio-dependent coordination modes in the formation of silver­(I) complexes are reported. 1H NMR and cold-spray-ionization mass spectrometry studies suggest that a silver­(I) complex with L gives different species depending on the molar ratio of silver ions used as the reactant. Furthermore, the conformation of cyclen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…The ligand ( L a and L b ) and AgOTf solutions were prepared with concentrations of 8.3 × 10 –3 and 5.0 × 10 –1 M, respectively. The proton signals at the 2- and 6-positions of the aromatic side arms (H a , H b , and H c protons) of L a should shift to higher field if these aromatic side arms cover the Ag + inclusion in the cyclen. As shown in Figure , the H a , H b , and H c protons shifted to a higher field with the addition of Ag + , and the chemical shift changes stopped when 2 equiv of Ag + was added (H a , −0.85 ppm; H b , −0.12 ppm; H c , −0.45 ppm). The result shows that the aromatic rings cover the Ag + ions incorporated in the cyclen rings in the presence of 2 equiv of Ag + .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ligand ( L a and L b ) and AgOTf solutions were prepared with concentrations of 8.3 × 10 –3 and 5.0 × 10 –1 M, respectively. The proton signals at the 2- and 6-positions of the aromatic side arms (H a , H b , and H c protons) of L a should shift to higher field if these aromatic side arms cover the Ag + inclusion in the cyclen. As shown in Figure , the H a , H b , and H c protons shifted to a higher field with the addition of Ag + , and the chemical shift changes stopped when 2 equiv of Ag + was added (H a , −0.85 ppm; H b , −0.12 ppm; H c , −0.45 ppm). The result shows that the aromatic rings cover the Ag + ions incorporated in the cyclen rings in the presence of 2 equiv of Ag + .…”
Section: Resultsmentioning
confidence: 99%
“…We have recently reported “argentivorous molecules”, in which the aromatic side arms cover silver­(I) bound in the cyclen moiety by weak coordination. In the argentivorous molecules, when silver ions are trapped in the cyclen moiety, the aromatic side chains move as if they were trapping insects by Ag + –π interactions with the aromatic rings of the side chains and CH−π interactions between the side arms. There are two conformations of the aromatic side arms in silver­(I) complexes with argentivorous molecules. As shown in Figure , the silver complex with an argentivorous molecule having benzyl side arms exists as a racemic mixture of Δ and Λ forms in solution and the solid state. More recently, we reported that introducing chirality into the cyclen ring or one of the methylenes of the side chain gave one isomer with the conformation of the side arms controlled in one direction according to the stereochemistry of the chiral carbon. , In particular, when chirality is introduced into the cyclen ring, the cyclen can form complexes with Ag + on both the front and back sides …”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, our group is interested in tetra-armed cyclens and their silver­(I) complexes, incorporating tetra-armed aromatic side chains, giving wide structural diversity in the resulting argentivorous molecules by Ag + –π and CH−π interactions. For example, we demonstrated that double- and tetra-armed cyclens bearing an anthracene or pyrene unit as side arms behave like an insectivorous plant (Venus flytrap) by Ag + –π interactions. More recently, we reported that an Ag + complex with tetra-armed cyclens with styrylmethyl groups incorporates chiral alkyl nitriles to afford a drastic enhancement of the molar ellipticity in CD spectra …”
Section: Introductionmentioning
confidence: 99%
“…Titration experiments were carried out using 1 H NMR spectroscopy to confirm the structures in a solution of Ag + complexes with the new ligands ( L1 – L5 ) (Figures and S6–S9). If the four aromatic side-arms cover the Ag + inclusion in the cyclen, the proton signals at the 2- and 6-positions (the H a protons in Figure ) of the aromatic side-arms should shift to a higher field. The spectral changes of the aromatic ring protons of L5 are shown in Figure . Upon the addition of Ag + , a higher-field shift and a lower-field shift of the H a and H b protons were observed.…”
Section: Resultsmentioning
confidence: 99%
“…In connection with argentivorous molecules, we have developed new functional molecules using cyclen with aromatic side-arms. In this study, we designed a new type of argentivorous molecule that introduced an oxyethylene chain at the 4-position of the aromatic side-arms as a secondary recognition site. We expected that the complexation of the cyclen moiety with silver ions would change the aromatic side-arms’ conformation and that the four oxyethylene chains would be arranged to surround the second metal cation.…”
Section: Introductionmentioning
confidence: 99%